2015
DOI: 10.12911/22998993/1861
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Diesel Oil in Soil and Its Enhancement by Application of Bioventing and Amendment With Brewery Waste Effluents as Biostimulation-Bioaugmentation Agents

Abstract: The purpose of this study is to investigate and evaluate the effects of natural bioattenuation, bioventing, and brewery waste effluents amendment as biostimulation-bioaugmentation agent on biodegradation of diesel oil in unsaturated soil. A microcosm system was constructed consisting of five plastic buckets containing 1 kg of soil, artificially contaminated or spiked with 10% w/w of diesel oil. Biodegradation was monitored over 28 days by determining the total petroleum hydrocarbon content of the soil and tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
38
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 37 publications
6
38
0
1
Order By: Relevance
“…Adsorbed fuel residuals are biodegraded, and volatile compounds also are biodegraded as vapors move slowly through biologically active soil. Effective bioremediation of petroleum contaminated soil using bioventing has been proved by many researcher [84,85].…”
Section: Bioventingmentioning
confidence: 99%
“…Adsorbed fuel residuals are biodegraded, and volatile compounds also are biodegraded as vapors move slowly through biologically active soil. Effective bioremediation of petroleum contaminated soil using bioventing has been proved by many researcher [84,85].…”
Section: Bioventingmentioning
confidence: 99%
“…These constraints are driving a search for cheaper and more environmentally-friendly options. One such option is the use of organic wastes that could act as bulking agents and also supply nitrogen, phosphorus and hydrocarbondegrading microorganisms to enhance the remediation process [10]. In addition, it provides an efficient, eco-friendly, cost effective solid waste management option [11][12].…”
Section: Introductionmentioning
confidence: 99%
“…and C/N = 120 had the highest percentage of removed diesel oil and this trend continued throughout the test; • for microcosms with C/N = 180, the highest removal was always achieved with u% = 12% b.w. 9 15 60 1 10 15 120 11 11 15 180 5 12 15 300 5…”
Section: Diesel Oil Removal Efficiencymentioning
confidence: 99%
“…In this area, previous studies have demonstrated that good removal efficiency can be achieved when indigenous bacteria are stimulated with mineral salt media in order to aerobically biodegrade soil pollutants without any addition of other carbon sources [9,10].Given the multitude of findings, it can be useful to know the kinetics of the process for planning in situ remediation activities. Moreover, optimization of the process in terms of the optimal operative parameters for a given system of soil pollution can be of help to maximize the achievable results.Several studies [11][12][13][14][15] have shown that hydrocarbon removal can be modeled with first-or second-order reaction kinetics. The complexity of the biological process explains the different results produced by these models.…”
mentioning
confidence: 99%
See 1 more Smart Citation